The power of Drosophila in modeling human disease mechanisms - Esther M. Verheyen (The Company of Biologists, 2022)
Six years ago, DMM launched a subject collection called 'Drosophila as a Disease Model'. This collection features Review-type articles and original research that highlight the power of Drosophila research in many aspects of human disease modeling. In the ensuing years, Drosophila research has further expanded to capitalize on genome editing, development of resources, and further interest in studying rare disease mechanisms. In the current issue of DMM, we again highlight the versatility, breadth, and scope of Drosophila research in human disease modeling and translational medicine. While many researchers have embraced the power of the fly, many more could still be encouraged to appreciate the strengths of Drosophila and how such research can integrate across species in a multi-pronged approach. Only when we truly acknowledge that all models contribute to our understanding of human biology, can we take advantage of the scope of current research endeavors.